Magic Embodied: The Future is Black Girl Magic - Szendrei, Bianka (Hungarian Journal of English and American Studies, 2022)
Book review:Jordan-Zachery, Julia S. and Duchess Harris, eds. Black Girl Magic Beyond the Hashtag: Twenty-First-Century Acts of Self-Definition. Tucson: U of Arizona P, 2019. 216 pages, ISBN 9780816539536. Pbk. $19.95.